Guests Perceptions And Expectation Of The Quality Of Service Of The Waiter And Waitress At Restoran Old Man’s Batu Bolong Canggu, Badung Bali - Yudha, Putu Dharma; Putra, Agus Muriawan; Sulistyawati, Agung Sri (Jurnal Kepariwisataan dan Hospitalitas, 2019)
As a one of the tourism industry which prioritizes service. Restaurant Old Man’s Batu Bolong faced some problems in its operations. There were some negative guest comment on the performance of the waiters or waitress such as dishes were not in accordance with what was ordered,grooming isn’t good, lack of waiter or waitress to explain the menu and then it hasn’t yet been able to explain the menu clearly to the guest. There is data of negative guest comment, this study aim to know guest perceptions of the quality of service of the waiter and waitress at Restoran Old Man’s Batu Bolong. This study were used the method of likert scale analysis and method of importance performance analysis by distributing a questionnaire containing 25 question take from the five dimensions of the service quality (tangible, reliability, responsiveness, assurance, empathy). Technique determination of informants was used purposive sampling, and the sampling of 100 respondents using accidental sampling technique. After measuring the satisfaction of tourist, it was obtained the level of concordance between the performance and the importance of 88,76 percent which means the guests were very satisfied of the quality of service of the waiter and waitress at Restoran Old Man’s Batu Bolong, but still there were sub-indicators which still considered to be fairly good so that it hasn’t been able to statisfy the guest. Based on the results of these measurements, the waiter and waitress are suggested to improve their quality of service performance were prioritized such as waiter and waitress looks wearing uniform, personal hygiene of the waiter and waitress, speed of waiter and waitress take an order, the abilities of the waiter and waitress to explain the menu so can’t to explain the menu clearly to the guest.   Keywords: Tourist Perception, Quality of Service, Restaurant.